Potency of Phitofert in Improvement of Reproductive Efficacy in Sulpiride-Treated Rats - Nahla J. M. S. Al-Shahery (Journal of Global Pharma Technology, 2018)
The current study was designed to investigate the persisting of hyperprolactinaemic (Hprl) symptoms because the impact longstanding of sulpiride injection (the 2nd model of Hprl), to prove these symptoms when they compared with these in 1st model of Hprl. Also we investigated whether Hprl had ablility to induce altering in the activity of ovarian hydroxy steroid dehydrogenase (HSD) enzymes and oxidative status in the ovarian tissue. The goal of this study was to evaluate the potentiality of phitofert product in adjustment of Hprl status for each 2nd model of Hprl. Therefore, female rats were divided as follows: G1: female rats were injected with normal saline (0.9% NaCl) for 28 successive days (control1). G2: female rats were injected with 40 mg/kg b.w. of sulpiride for 28 successive days (as a first model). G3: female rats were injected with normal saline (0.9% NaCl) for 28 successive days, and they were orally administrated with d.w. for another 28 successive days (control2). G4: female rats were injected with 40 mg/kg b.w. of sulpiride for 28 successive days, and they were orally administrated for another 28 successive days with d.w. (as a second model). G5: female rats were injected with 40 mg/kg b.w. of sulpiride for 28 successive days, and they were orally administrated with 7 mg/kg b.w. of phitofert for another 28 successive days. The hyperprolactinaemia signs primarily a significant (P≤ 0.05) elevation in the serum prolactin (Prl) and progesterone (P) levels were found, while the serum FHS, LH and estrgen levels were found to be significantly (P≤ 0.05, P≤ 0.001) decreased in G2 and G4 than controls (G1and G3). The hyperprolactinaemic rats (G2 and G4) also, showed a significant (P≤ 0.05) decreased in the activity of an ovarian 20α-HSD enzyme, compared to G1 and G3. The oxidative stress (OS) as evidenced by significantly (P≤ 0.05) increased in the activity of lipid peroxidation (MDA) and decreased in the ovarian activity of GSH and CAT levels were found in these groups.  Also the estrus cycles and ovulation process were ceased in hyperprolactinemic groups (G2 and G4). Whereas the results of G5 showed that, the phitofert had a positive role in the reverse of all above assessed parameters in sulpiride-induced hyperprolactinemia groups. The phitofert treatment resulted regular estrus cycle and the restoration of ovulation, ditto the ovulated oocytes were able to fertilize in vitro. These fertilized oocytes of G5 were succeeded in the development in vitro to blastocyst stages. So the transferred blastocysts into recipient females were able to implantation compared to those in control (G3). Thus, our findings proved the ability of phitofert product in therapy of HPRL.